A COMPARATIVE STUDY ON PREVALENCE OF STROKE AND ASSOCIATE PROBLEMS AMONG PHYSICALLY ACTIVE ADULTS AND SEDENTARY ADULTS – A REVIEW - Indrajit Karmakar,; Jagannath Ghosh, (The Bioscan, 2024)
Stroke, a clinically identified disorder mostly common among the sedentary adult individuals nowadays due to their sedentary lifestyle, smoking, alcohol abuse and also associated with nonmodifiable factors like character, inherited attributes, family history, genetics. Physical activity plays a crucial role in stroke prevention and in rehabilitation. Regular exercise improves cardiovascular health, reduces risk factors of stroke, and promotes better outcomes among stroke survivors. This meta-analysis indicates a significant reduction in stroke incidence and mortality among physically active individuals. Conversely, sedentary behaviour increases stroke risk. Research states the need for tailored interventions promoting physical activity and healthy lifestyles to reduce stroke burden. While this review sheds light on the relationship between physical activity and stroke, limitations include variations in study methodologies and measurement tools. Addressing these limitations can refine our understanding and enhance stroke prevention and rehabilitation strategies, ultimately improving long-term outcomes for individuals at risk and will also help in further research.